Dietary ingestion of 2-aminoanthracene (2AA) and the risk for type-1 diabetes (T1D). Issue 14 (12th October 2020) - Seise, Isaiah; Pilz, Zachary A.; Kusi, Moses Yeboah; Bogan, Bethany; McHale, Brittany Jean; Gato, Worlanyo E.
Abstract: Type 1 diabetes (T1D) is an autoimmune disorder caused by the destruction of insulin-secreting β-cells.T1D is on the rise around the world. Exposure to polycyclic aromatic hydrocarbons (PAHs) including 2-aminoanthracene (2AA) is considered a contributor to TID increase. The contribution of the ingestion of 2AA toward T1D vulnerability is examined. 2AA is found in a variety of household products. Juvenile male Sprague Dawley rats ingested various amounts of 2AA contaminated diet for 12 weeks. Results showed marginal reduction in body weight gain for the 100 mg/kg treated animals. Glucose tolerance test (GTT) indicated no changes at six weeks. However, at week 12, both treated groups had higher levels of blood glucose than the control group. Serum insulin concentration was elevated in the 50 mg/kg group while reduced in the 100 mg/kg animals. Serum lactate dehydrogenase activity was elevated in treated groups. Evaluation of pancreatic inflammatory cytokines revealed overexpression of IL-1B, IL-6, and IL-7. Apoptotic genes in the pancreas of exposed rats were overly expressed. Histopathology and insulin immunohistochemistry data showed the presence of mesenteric vessels surrounded by lymphocyte and enlarged size of islet cells respectively in the high dose group. These results suggest 2AA ingestion may enhance T1D development.